2017
DOI: 10.1016/j.japh.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence, molecular monitoring, and clinical outcomes in patients with chronic myelogenous leukemia in a large HMO

Abstract: Our results suggest that close clinical monitoring, which includes PCR monitoring in patients with high and low TKI drug adherence, is associated with a lower risk of progression or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 17 publications
2
47
0
Order By: Relevance
“…In one study, comparing 3 to 4 annual qPCR tests with no annual qPCR tests was found to yield a significant reduction in disease progression . However, in another study, 1 to 2 annual qPCR tests did not appear to reduce disease progression significantly . The results of the current study provide greater granularity to these findings in that even one tPCR may lead to better outcomes for patients.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In one study, comparing 3 to 4 annual qPCR tests with no annual qPCR tests was found to yield a significant reduction in disease progression . However, in another study, 1 to 2 annual qPCR tests did not appear to reduce disease progression significantly . The results of the current study provide greater granularity to these findings in that even one tPCR may lead to better outcomes for patients.…”
Section: Discussionmentioning
confidence: 49%
“…8 However, in another study, 1 to 2 annual qPCR tests did not appear to reduce disease progression significantly. 14 The results of the current study provide greater granularity to these findings in that even one tPCR may lead to better outcomes for patients. It is interesting to note that the results of the current study demonstrate that patients who have timely monitoring also tend to have more frequent monitoring.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Another potential approach for an OCM to reduce the total cost of care of CML patients might be to improve the frequency of molecular monitoring, since several studies have reported routine molecular monitoring is associated with improved patient outcomes, which could lead to a reduction in healthcare costs [27][28][29][30][31][32][33] . Two separate studies have also reported cost reductions associated with earlier and more frequent monitoring of CML patients to proactively manage TKI treatment responses 31,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Tolerability Detailed data on adverse events occurring early during treatment 22 Treatment discontinuation 22,25,26 Long-term treatment side effects and complications 39 CML research studies Response Molecular, cytogenetic, and hematologic response rates at discrete time points 22,25,26 Kinetics of reduction in BCR-ABL1 transcript levels 40 Assessment of whether a patient meets designated treatment response landmarks (eg, target response levels at 3, 6, and 12 months from the start of treatment) 40 Rates of CML progression at early time points 40 Development of evidence supporting new treatment practices, such as criteria for attempting treatment-free remission 34,41e47 Long-term treatment effects 27 Long-term rates of CML progression 32 Rates of treatment failure in clinical practice 14,30 Analysis of treatment switching patterns, including rates of treatment switch due to treatment failure 14,30 Analysis of treatment-free remission practices and outcomes in clinical practice 48 Outcomes in patients not typically included in RCTs 29,30 Response rates in clinical practice 31 Real-world disease management practices 31…”
Section: Qol 38mentioning
confidence: 99%